Violent conflict and the transformation of social capital lessons from Cambodia, Rwanda, Guatemala and Somalia - Colletta, Nat J.; Cullen, Michelle L. 1968- (Conflict prevention and post-conflict reconstruction, 2000)
In an effort to better understand the interactions between violent conflict and social capital, the authors undertook an exploratory investigation f four conflict-affected countries-Cambodia, Rwanda, Guatemala, and Somalia-and their changing social capital dynamics. The data for this report have been drawn from extensive literature reviews and from eight community-level studies conducted in the four countries. On this basis, the report discusses changes in social capital resulting from violent conflict; the interaction between social capital, social cohesion, and violent conflict; and how civil society, governments, and international actors can nurture the social capital needed to strengthen social cohesion and so promote conflict prevention, rehabilitation, and reconciliation. Findings and recommendations are preliminary, as each case study was conducted on an exploratory basis only. The study results are specific to the countries analyzed, although some broad generalizations may have wider validity.